Phonetic Difficulties Faced by Indonesian Speakers in Pronouncing Arabic Letters - Wahyu Suci Anggrayani (al-Afkar, Journal For Islamic Studies, 2025)
Arabic is a language with phonetic complexity and is a challenge for Indonesian speakers who learn it as a second language (L2). This study aims to identify phonetic differences between Arabic and Indonesian that cause difficulties in articulation, as well as to analyze the Arabic letters that are most difficult to pronounce for Indonesian speakers. Using a descriptive qualitative method based on library research, this study analyzed various literature sources related to phonetics and foreign language learning. The results of the study indicate that differences in phoneme structure, especially the presence of typical Arabic phonemes such as /ʕ/ (ain), /ħ/ (ḥa’), /q/ (qaf), and long vowels, are the main obstacles in the pronunciation process. Interference from the mother tongue (L1) also plays a significant role in articulation errors. To overcome these obstacles, it is recommended to use teaching strategies that focus on articulation exercises, a visual-auditory phonetic approach, and the use of interactive technology to improve pronunciation accuracy and the effectiveness of Arabic language learning. This study makes an important contribution to the development of more adaptive Arabic language teaching methods for Indonesian speakers.